Association between CYP17A1 rs3824755 and rs743572 gene polymorphisms and Alzheimer's disease in the Chinese Han population. (8th April 2016) - Xie, Li; Yan, Huacheng; Shi, Lei; Kong, Yanying; Huang, Mukun; Li, Jian; Li, Jin; Zheng, Jiaqiang; Zhao, Yongpan; Zhao, Shujin
Highlights: The relationship between CYP17A1 polymorphisms and AD was examined in Han Chinese. CYP17A 1 rs3824755C allele/GC + CC genotypes protect against AD in APOE e4 carriers. CYP17A1 rs743572 G allele and AG + GG genotypes act synergetically with APOE e4. CYP epoxygenase hormone synthesis pathway is a critical factor in AD pathogenesis. Abstract: The CYP17A1 gene encodes cytochrome P450c17α, an enzyme that catalyzes the formation of sex hormones, which have been linked to the pathogenesis of Alzheimer's disease (AD). An association between the CYP17A1 rs743572 single nucleotide polymorphism (SNP) and AD has been reported; however, the findings are controversial. In the present study, we investigated the association between rs743572 and another SNP, rs3824755, and AD risk in a Chinese Han population (n = 207 patients and 239 controls), and their interaction with the apolipoprotein E ( APOE ) e4 allele. We found that the C allele and GC + CC genotypes of rs3824755 conferred protection against AD only in APOE e4 carriers. Both rs3824755 and rs743572 polymorphisms showed interactions with APOE e4. The C allele and GC + CC genotypes of rs3824755 acted as protective factors that decreased the risk of APOE e4 in AD. The CYP17A1 rs743572 G allele and AG + GG genotypes were found to be potential risk factors that act synergetically with APOE e4. Moreover, the CA and GG haplotypes were protective and conferred a slight risk, respectively, in APOE e4 carriers. These results indicate that CYP17A1 rs3824755 and rs743572 are associated with AD in the Chinese Han population and act in combination with APOE e4.